2019
DOI: 10.1016/j.jhevol.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

First metatarsal trabecular bone structure in extant hominoids and Swartkrans hominins

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 162 publications
(253 reference statements)
0
15
0
Order By: Relevance
“…As suggested by previous research, Plio-Pleistocene hominins practiced different forms of terrestrial bipedality (e.g., Stern, 2000;Ward, 2002Ward, , 2013Lovejoy et al, 2009;Haile-Selassie et al, 2012;Barak et al, 2013;DeSilva et al, 2012DeSilva et al, , 2013Harcourt-Smith, 2016;Ruff et al, 2016Ruff et al, , 2018Zeininger et al, 2016), likely implying slightly different gait kinematics (Komza and Skinner, 2019). Evidence for some variations between A. africanus and Paranthropus has been provided by the study of the trabecular architecture of the hip bone (Macchiarelli et al, 1999) and of the talus (Su and Carlson, 2017), while no textural differences have been found between the two taxa at the femoral head (Ryan et al, 2018).…”
Section: Discussionmentioning
confidence: 80%
“…As suggested by previous research, Plio-Pleistocene hominins practiced different forms of terrestrial bipedality (e.g., Stern, 2000;Ward, 2002Ward, , 2013Lovejoy et al, 2009;Haile-Selassie et al, 2012;Barak et al, 2013;DeSilva et al, 2012DeSilva et al, , 2013Harcourt-Smith, 2016;Ruff et al, 2016Ruff et al, , 2018Zeininger et al, 2016), likely implying slightly different gait kinematics (Komza and Skinner, 2019). Evidence for some variations between A. africanus and Paranthropus has been provided by the study of the trabecular architecture of the hip bone (Macchiarelli et al, 1999) and of the talus (Su and Carlson, 2017), while no textural differences have been found between the two taxa at the femoral head (Ryan et al, 2018).…”
Section: Discussionmentioning
confidence: 80%
“…When comparing differences in Tb.Th, Tb.N, and Tb.Sp across our study sample, results were similar to those of previous studies of different skeletal elements; Pan had high Tb.N and low Tb.Th and Tb.Sp, Gorilla showed the inverse, while Homo and Pongo were intermediate for all of these measures (Georgiou et al, 2019 ; Georgiou et al, 2018 ; Kivell et al, 2018 ; Komza & Skinner, 2019 ; Ragni, 2020 ; Ryan & Shaw, 2015 ; Scherf et al, 2013 ; Schilling et al, 2014 ). The consistent pattern within these parameters may represent systemic, rather than strongly functionally adaptive features of bone.…”
Section: Discussionmentioning
confidence: 99%
“…As functional adaptation research aims to identify markers of behavior rather than body size, analyzing bone parameters for allometric effects has been integral to interspecific analyses (Ruff, 1984 ). Decades of research across various species has yet to find consistent patterns; however, some research suggests there may be a general pattern across mammals and birds whereby bone volume to total volume (BV/TV) and degree of anisotropy (DA) are independent of body mass (Barak et al, 2013 ; Christen et al, 2015 ; Cotter et al, 2009 ; Doube et al, 2011 ; Kivell et al, 2018 ; Komza & Skinner, 2019 ; Schilling et al, 2014 ; Tsegai et al, 2017 ) while trabecular thickness (Tb.Th), trabecular number (Tb.N) and trabecular separation (Tb.Sp) scale with negative allometry (Barak et al, 2013 ; Kivell et al, 2018 ; Ragni, 2020 ; Ryan & Shaw, 2013 ). Cortical thickness (Ct.Th) is often reported to be isometric or slightly positively allometric (Demes et al, 2000 ; Fajardo et al, 2013 ; Runestad, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain aspects of foot morphological variation, such as that in the talus and metatarsals, have been heavily scrutinized (e.g., Boyer, Yapuncich, Butler, Dunn, & Seiffert, 2015; Kanamoto, Ogihara, & Nakatsukasa, 2011; Komza & Skinner, 2019; Latimer, Ohman, & Lovejoy, 1987; Susman & Brain, 1988). Latimer et al (1987), for example, found that gorillas, chimpanzees, and modern humans possess different apical angles of the talar trochlea, which they argued to be related to locomotor behavior and the ability to medially and laterally rotate the foot during plantarflexion and dorsiflexion, respectively.…”
Section: Introductionmentioning
confidence: 99%